Potential Development of a Mobile Application for Gout Self-Management: What Support Do Patients Need? [Corrigendum] - Yin Y (Dove Medical Press, 2021)
Yin Y, Wang H, Fan CF, Chen H. Patient Prefer Adherence. 2021;15:2231–2238. The authors have advised affiliation 1 on page 2231 is incorrect. The text “Department of Neurology/Evidence-based Nursing Center” should read “Department of Neurological Comprehensive Ward/Evidence-based Nursing Center”. The authors apologize for this error. Read the original article